Representing France and the French in early modern English drama - Mayer, Jean-Christophe (Univ. of Delaware Press, 2008)
Shakespeare, Burgundy, and the design in the arras / Dominique Goy-Blanquet -- Mary Sidney's French Sophocles : the Countess of Pembroke reads Robert Garnier / Anne Lake Prescott -- "Worthies away" : the scene begins to cloud in Shakespeare's Navarre / Richard Wilson -- George Chapman's French tragedies, or, Machiavelli beyond the mirror / Gilles Bertheau -- The ironies of Babel in Shakespeare's Henry V / Jean-Christophe Mayer -- "O confusion of languages, and yet no tower of Babel!" : French allusions and Ben Jonson's linguistic project / Florence March -- Roussillon and retrospection in All's well that ends well / Deanne Williams -- Strangers alter et idem : French allusions and the staging of distant lands in early modern drama / Ladan Niayesh -- The "French disease" in Elizabethan and Jacobean drama / Frederique Fouassier -- "False Frenchmen" in Richard Brome's plays / Athina Efstathiou-Lavabre